Prefabricated direct composite veneer: with and without teeth preparation - Azam Muhammad Aliuddin; Zafar Ali, Jabeen; Shiekh, Abubakar; Rashid, Saqib (International Journal of Endorsing Health Science Research, 2018)
Background: Componeer (prefabricated direct composite veneer) is a nano-hybrid composite enamel veneer that combines the advantages of both, placing a direct composite resin and those of a prefabricated laminate veneer manufactured in a laboratory. Any structural defects or anomalies in the anterior teeth or ‘esthetic zone’ create a problem for the patient. Hence, composite laminate veneers focus on targeting such abnormalities where the dentist is in complete control of the outcome, despite the pre-existing color, shape, structure, contours or morphology of the tooth. The aim of the study was to determine the success rate of using prefabricated direct composite veneers for cases with minimal preparation and ‘prep-less’ technique and compare both outcomes for establishing a better and long-lasting restoration. Case presentation: The study presented two case reports, the first case was of a 46-year-old female with major complaints regarding spaces between upper teeth along with yellow discoloration. While the second i.e. Case 2 was of a 23 years old female with generalized spacing in her teeth due to microdontia and her chief complaint was the diastema present in between her upper front teeth. Management and Results: A minimal preparation technique for composite veneering was used in Case 1 to combat the problem of yellow discoloration along with generalized spacing whereas a ‘prep-less’ technique was used for Case 2. Both cases depict different methods of composite veneering and restorations for both minimally prepared or ‘prep-less’ technique showed no differences at the follow-up visit (after 6-month). Conclusion: Composite veneers have shown excellent results for restoring anterior defects while preserving tooth structure and surrounding tissues. It has proven to be the most time-efficient way of restorations meeting the high demands of superior esthetics and cost-effectiveness.